Specific binding of murine leukemia inhibitory factor to normal and leukemic monocytic cells. - Hilton, D J (1988)
Leukemia inhibitory factor (LIF), a glycoprotein capable of suppressing the clonogenicity and inducing the differentiation of the murine myeloid leukemia cell line M1, was radioiodinated to a high specific radioactivity with retention of full biological activity. Binding of 125I-labeled LIF to M1 cells reached a steady state at 37 degrees C after approximately equal to 40 min and was in competition with unlabeled LIF but not granulocyte colony-stimulating factor or a range of other cytokines or differentiation-inducing agents. Specific binding was demonstrable to cells from a range of murine hemopoietic tissues including the bone marrow, the spleen, and the peritoneal cavity. Autoradiography revealed macrophages, monocytes, and their precursors to be the major cell types responsible for 125I-labeled LIF binding within these tissues. Receptors on M1 cells were of high affinity (apparent Kd, 100-200 pM) and few in number (300-500 per cell).